2020
DOI: 10.1155/2020/7397169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modeling of Football Team’s Collaboration Mode and Performance Evaluation Using Network Science and BP Neural Network

Abstract: With the continuous development of society, the cooperation of different dimensions is urgently needed. Analysis and modeling of team cooperation model and performance evaluation are especially important for competitive sport. In this paper, a football team’s attacking mode and the team performance were assessed using network science methodologies. The match process was analyzed by using the data of Team A (given in the form of attachment due to excessive file size) and the method of complex network sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The key to establishing a three-layer BP network model is the determination of the input layer's neuron number, the hidden layer's number, the hidden layer's neuron number, the selection of transferring function as well as the training function. The high nonlinear processing ability of BP neural network makes it widely applied in game prediction, and techniques and tactics diagnosis for ball matches [13,24,25]. Yang & Zhang used BP neural network and multiple regression to analyze the technical and tactical ability of elite male table tennis players, and the results showed that the overall fitting accuracy of the BP neural network was higher than that of the multiple regression model [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key to establishing a three-layer BP network model is the determination of the input layer's neuron number, the hidden layer's number, the hidden layer's neuron number, the selection of transferring function as well as the training function. The high nonlinear processing ability of BP neural network makes it widely applied in game prediction, and techniques and tactics diagnosis for ball matches [13,24,25]. Yang & Zhang used BP neural network and multiple regression to analyze the technical and tactical ability of elite male table tennis players, and the results showed that the overall fitting accuracy of the BP neural network was higher than that of the multiple regression model [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e network is a vital concept to understand modern society structure and components of the society. e concept of the network has been applied not only to people but also to social network [1][2][3][4][5][6][7], biological network [8][9][10][11][12], metabolic regulation network [13], online social network [14,15], sports social network [16,17], structure of neural network [18][19][20], etc. As a result, the data for storing network information has become complex and diverse.…”
Section: Introductionmentioning
confidence: 99%